The institutions of archaic post-modernity and their organizational and managerial consequences: The case of Portugal - Pina e Cunha, Miguel (2014)
The long march of modernization of the Western societies tends to be presented as following a regular sequence: societies and institutions were pre-modern, and then they were modernized, eventually becoming post-modern. Such teleology may provide an incomplete or distorted narrative of societal evolution in many parts of the world, even in the ‘post-modern heartland’ of Western Europe, with Portugal being a case in point. The concept of archaic post-modernity has been developed by a philosopher, José Gil, to show how Portuguese institutions and organizations combine elements of pre-modernity and post-modernity. The notion of an archaic post-modernity is advanced in order to provide an alternative account of the modernization process, which enriches discussion of the varieties of capitalism. Differences in historical experiences create singularities that may be considered in the analysis of culture, management and organization.